Nomenclatural notes on Tectaria blepharorachis (comb. nov.) and T. fibrillosa (Tectariaceae; Pteridophyta) for Malagasy fern flora - Duan, Yi-Fan; Zhang, Libing (Phytotaxa, 2014)
While working on a monograph of Ctenitis (Dryopteridaceae) found in Madagascar we discovered that two Tectaria-related names need nomenclatural attention: the name C. poolii (C.Christensen) Tardieu-Blot is not legimate, and Dryopteris blepharorachis C.Christensen should be reinstalled from synonymy. A new combination, Tectaria blepharorachis (C.Christensen) Li Bing Zhang & Yi F. Duan, is proposed. Line drawings of pinnae of the both related species are provided for identification purpose.